Mediating Role of Locus of Control in the Relationship Between Emotional Intelligence and Employee Acceptance to Change - Singh, Priyanka; Upadhyay, Rajesh Kumar; Srivastava, Monika (Prabandhan: Indian Journal of Management, 2019)
Change is inevitable, and organizations have to understand it. However, it is not possible until the employees of the organizations embrace the change. Thus, the present study attempted to investigate the influence of Locus of Control and Emotional Intelligence (EI) on Employees' Acceptance to Change. The data were obtained from the survey of faculties from institutions of higher education in India. Mediation measurement was conducted using AMOS to investigate the effect of Locus of Control on the relationship between Emotional Intelligence and Employees' Acceptance to Change, and a profound impact was observed from the study. The study explained the role of the psychological variables in implementing change in the organization by suggesting that the management should implement planned training of emotional intelligence for faculties, deploying participation, facilitation, negotiation strategies, and strengthening the communication channels for catalyzing smooth change in organizations.